Seroprevalance of transfusion transmissible infected blood donors in northern Pakistan - Azeem, Rashid (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
BACKGROUND: Transfusion transmitted infections need a serious monitoring as it can be transmitted through apparently fit blood donors and threatens health of patients requiring transfusion. Economically it imposes inconveniences for the accessibility of safe blood products in medical services with limited resources. OBJECTIVE: The aim of the present study is to evaluate the seroprevalence of TTIs among the apparently fit and asymptomatic blood donors in Northern Pakistan. MATERIALS AND METHODS: A prospective observational study was conducted in 6 public, 1 private and 2 standalone blood banks from 1st January 2012 to 31st December 2013. Screening for Hepatitis B surface antigen, Anti HCV and Anti HIV was done by ELISA methods. Syphilis was screened by rapid plasma reagin (RPR) and malaria was done by thick film and immunochromatographic method. RESULTS: A total of 204942 donors donated blood were screened. Males comprised 98.7% while females were only 1.3%. Maximum blood donors were in the age group of 18-29 years (59.4%) followed by 30-49 years(40.1%) and 0.5% age >50 years. A total of 3.9% (n=8034) were infected for TTIs. HBV infection was most common 2.07% (n=4253), second was HCV 1.5% (n= 3189) followed by syphilis 0.16% (n=340), malaria 0.16% (n=340) and HIV 0.07% (n=144). CONCLUSION:This is the first local study done on such high scale in Northern Pakistan showing the prevalence of TTIs in donor population. There is need of stringent donor selection criteria along with emphasis on voluntary blood donation and use of standardized methods for screening TTIs in blood donors.